Connecting teachers in remote Australia: Challenges in realising the potential of videoconferencing - Reading, C.; Fluck, A.; Trinidad, Sue; Anderson, N.; White, B. (Australian Council for Computers in Education, 2008)
Most teachers recognise the benefits of meeting face-to-face for professional learning activities. However, for teachers in remote locations in Australia the vast distances that need to be travelled for such meetings are prohibitive. Videoconferencing has the potential to provide these teachers with quality professional learning experiences. This paper aims to highlight the challenges that inhibit the use of videoconferencing for professional learning experiences for those most likely to benefit, the teachers in remote schools. Firstly, is a description of the potential for the use of videoconferencing to enable and enhance professional learning experiences for teachers, especially in remote locations. Secondly, is a synopsis of the videoconferencing facilities available for teachers in schools in each of the five states involved in the national project. Especially important is the difference between what is possible for remote schools compared to their urban counterparts. Thirdly, is the anticipated professional connection of teachers in a national project on the use of social computing to enhance learning in remote Australia. Finally, the actual experiences of teachers from the schools in each state involved in the project shows how the challenges of remote location connection to videoconference links hampered teacher participation in the professional learning experiences.